INCREASING STUDENTS' LEARNING MOTIVATION WITH THE APPLICATION OF QR CODE-BASED LEARNING GAMES: ADVENTURES IN SEARCH OF PANCASILA TREASURES IN CLASS VIII.4 SMP NEGERI 30 PALEMBANG - Kholish, Ahmad Al; Faisal, Emil El; Reza, Intan Mei; Mulia, Mauli; Ramadhani, Qori (JURNAL SOCIUS, 2025)
This research aims to increase the learning motivation of students in grade VIII.4 of SMP Negeri 30 Palembang in the subject of Pancasila Education through the application of the QR-Code-based Game Based Learning method: Adventure in Search of Pancasila Treasures. This research uses Classroom Action Research (PTK) which is carried out in two cycles, each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of the study were 36 students who took place from July to August 2024. The results showed a significant increase in students' motivation to learn. In the first cycle, the students' learning motivation was recorded at 41%, while in the second cycle it increased to 75%. The  QR Code-based Game Based Learning  method is effective in increasing student learning motivation in a fun and interactive way. This study concludes that the use of this method can help increase students' motivation and learning performance, especially in understanding Pancasila Education material. The authors recommend the use of similar methods in research or learning in other subjects for optimal results.